Upside risk, consumption value, and market returns to food safety. Issue 3 (2nd October 2022) - Hoffmann, Vivian; Kariuki, Sarah; Pieters, Janneke; Treurniet, Mark
Abstract: We investigate the effect of a modest food safety premium on semisubsistence farmers' investment in a food safety technology. We demonstrate theoretically that in the face of production uncertainty, a market incentive below the marginal production cost of achieving the safety standard can increase food safety investment among farmers motivated by private health returns. We test this prediction through a randomized controlled trial in Kenya through which members of existing farmer groups were offered an opportunity to purchase a food safety input, and half were offered a 5% market premium for produce that met the associated regulatory standard. Access to the premium more than doubled investment in the food safety technology. In line with the model's prediction, most premium‐induced adoption was by farmers motivated by a combination of health and financial rewards.